Phosphate solubilizing bacteria (PSB) and commercial rock phosphate: an effective combination for oil palm nursery - Haoran, Ding; Tan, Geok Hun; Kasim, Susilawati (Universiti Putra Malaysia, 2025)
The growth of oil palm trees depends on phosphate availability. Phosphate-solubilizing bacteria (PSB) enhance the availability of phosphorus from phosphate rock by its phosphorus solubilizing ability. Phosphate solubilizing bacteria (PSB) can improve the available phosphorus content provided by phosphate rock through its phosphorus solubilization ability. In the management of palm tree nurseries, it is vital to carefully choose the appropriate type and application rate of phosphate fertilizers based on the growth requirements and soil characteristics of palm saplings to achieve optimal growth outcomes. The purpose of this study was to determine how well oil palm nursery could benefit from the use of commercial rock phosphate in conjunction with phosphate-solubilizing bacteria (PSB). Bacillus marisflavi and Bacillus aryabahattai populations in 1 g of compost were found to be 2 × 109and 1 × 108respectively, using the plate count method. As seen by leaf count, oil palm size, and frond height, the development rate and quality of oil palm seedlings are greatly enhanced by the combination of Morocco rock phosphate (MRP) and PSB. This study demonstrated that a combination of PSB and commercial phosphate rock is beneficial to oil palm seedlings and sought to determine its efficacy in oil palm nurseries.